Vitamin D opposes multilineage cell differentiation induced by Notch inhibition and BMP4 pathway activation in human colon organoids - Pilar Bustamante-Madrid; Antonio Barbáchano; David Albandea-Rodríguez; Javier Rodríguez-Cobos; Nuria Rodríguez-Salas; Isabel Prieto; Aurora Burgos; Jaime Martínez de Villarreal; Francisco X. Real; José Manuel González-Sancho; María Jesús Larriba; Miguel Lafarga; et al. (Cell Death and Disease, 2024)
Abstract Understanding the mechanisms involved in colonic epithelial differentiation is key to unraveling the alterations causing inflammatory conditions and cancer. Organoid cultures provide an unique tool to address these questions but studies are scarce. We report a differentiation system toward enterocytes and goblet cells, the two major colonic epithelial cell lineages, using colon organoids generated from healthy tissue of colorectal cancer patients. Culture of these organoids in medium lacking stemness agents resulted in a modest ultrastructural differentiation phenotype with low-level expression of enterocyte (KLF4, KRT20, CA1, FABP2) and goblet cell (TFF2, TFF3, AGR2) lineage markers. BMP pathway activation through depletion of Noggin and addition of BMP4 resulted in enterocyte-biased differentiation. Contrarily, blockade of the Notch pathway using the γ-secretase inhibitor dibenzazepine (DBZ) favored goblet cell differentiation. Combination treatment with BMP4 and DBZ caused a balanced strong induction of both lineages. In contrast, colon tumor organoids responded poorly to BMP4 showing only weak signals of cell differentiation, and were unresponsive to DBZ. We also investigated the effects of 1α,25-dihydroxyvitamin D3 (calcitriol) on differentiation. Calcitriol attenuated the effects of BMP4 and DBZ on colon normal organoids, with reduced expression of differentiation genes and phenotype. Consistently, in normal organoids, calcitriol inhibited early signaling by BMP4 as assessed by reduction of the level of phospho-SMAD1/5/8. Our results show that BMP and Notch signaling play key roles in human colon stem cell differentiation to the enterocytic and goblet cell lineages and that calcitriol modulates these processes favoring stemness features.